Analisis Pendapatan dan Belanja Desa di Desa Tegalrejo Kecamatan Tugumulyo Kabupaten Musirawas - Ricci Dwi Mahgfiro; Edduar Hendri; Reva Maria Valianti (Jurnal Media Akuntansi (Mediasi), 2023)
ABSTRACT This study aims to analyze Village Income and Expenditures in Tegalrejo Village, Tugumulyo District, Musirawas Regency per year, to determine the increase and decrease in village income and expenditure and whether their management is in accordance with the principles of Village financial management, namely Participatory, Transparency and Accountability and Discipline. Budget. This research was conducted using a qualitative descriptive method and data collected through observation, interviews, and documentation. The data is in the form of an archive of reports on the realization of the Village Budget for 2019,2020, 2021, the results of the description are obtained through a comparison of Permendagri No. 113 of 2014 with facts and conditions in the Tegalrejo Village. The results of the study show that the management of Village Finance, especially Village Income and Expenditures in the Tegalrejo City Village in general, has followed the Minister of Home Affairs Regulation and the Law governing Village finances, and has implemented the principles of Village financial management, namely Participatory, Transparency and Accountability and Discipline. Budget. Keywords: Village Income and Expenditure, Participatory, Transparent and Accountable, Budget Discipline. ABSTRAK Penelitian ini bertujuan untuk menganalisis Pendapatan dan Belanja Desa di Desa Tegalrejo Kecamatan Tugumulyo Kabupaten Musirawas per tahunya, untuk mengetahui peningkatan dan penurunan pendapatan dan belanja desa dan pengelolaanya apakah sudah sesuai dengan asas pengelolaan keuangan Desa yaitu Partisipatif, Transfaran dan Akuntabel serta Disiplin Anggaran. Penelitian ini dilakukan dengan menggunakan Metode deskriptif kualitatif dan data dikumpilkan melalui Observasi, wawancara, dan dokumentasi. Data berupa arsip laporan realisasi Anggaran pendapatan dan Belanja desa tahun 2019,2020,2021, hasil deskripsi didapat melalui perbandingan Permendagri No 113 Tahun 2014 dengan fakta dan Kondisi yang ada di Desa Tegalrejo. Hasil Penelitian menunjukan bahwa pengelolaan Keuangan Desa khususnya Pendapatan dan Belanja Desa di Desa Tegalrejosecara garis besar telah mengikuti Peraturan Mentri dalam Negri dan Undang-Undang yang mengatur tentang keuangan Desa, dan telah menerapkan asas pengelolaan keuangan Desa yaitu Partisipatif, Transfaran dan Akuntabel serta Disiplin Anggaran. Kata kunci: Pendapatan dan Belanja Desa, Partisipatif, Transparan dan Akuntabel, Disiplin Anggaran.